No easy balancing act: Reducing the balance of payments constraint; improving export competitiveness and productivity; and absorbing surplus labor - the Indian experience - Suranjana Nabar-Bhaduri (The University of Utah, Department of Economics, 2011)
As per the balance of payments constraint hypothesis, in an open economy, achieving a high long-run rate of growth would require a country to reduce its balance of payments constraint through an improved export performance, and the production of import substitutes, which would lower the income elasticity of demand for imports. While a reduction of the balance of payments constraint is crucial for developing countries, in these countries, a sustainable and inclusive process of growth and development also requires the generation of high productivity activities, quality employment, and greater domestic value-added. By focusing on the Indian case, this paper shows that even if a developing country manages to reduce its balance of payments constraint, concentrated improvements in productivity and employment may remain at the industrial level. Consequently, active policy efforts to generate quality employment on a wide scale and to improve the productivity in different industrial and agricultural activities would remain crucial. Furthermore, as has been the case in India, this paper also shows that a reduction of the balance of payments constraint may be more the result of an improvement in the net exports of services, than an improvement in the external competitiveness of merchandise exports. As such, a country may exhibit trade balance deficits over a long period of time, thereby showing an increase in its external debt obligations. This then raises the question of whether a higher rate of growth facilitated by a reduction of the balance of payments constraint can be sustainable in the long-run. Even if the ability to service the external debt shows an improvement over time, such a services-led reduction of the balance of payments constraint may not necessarily address the more crucial problem of generating quality employment to make the process of growth more inclusive.
Keywords: F14; F41; F43; O11; O12; O14; 330; balance of payments constraint; export dynamics; technology gaps; import content of exports; structural heterogeneity; services-led growth.